The relative contribution of methanotrophs to microbial communities and carbon cycling in soil overlying a coal‐bed methane seep. Issue 3 (19th February 2013) - Mills, Christopher T.; Slater, Gregory F.; Dias, Robert F.; Carr, Stephanie A.; Reddy, Christopher M.; Schmidt, Raleigh; Mandernack, Kevin W.
Abstract: Seepage of coal‐bed methane (CBM) through soils is a potential source of atmospheric CH4 and also a likely source of ancient (i.e. 14 C‐dead) carbon to soil microbial communities. Natural abundance 13 C and 14 C compositions of bacterial membrane phospholipid fatty acids (PLFAs) and soil gas CO2 and CH4 were used to assess the incorporation of CBM‐derived carbon into methanotrophs and other members of the soil microbial community. Concentrations of type I and type II methanotroph PLFA biomarkers (16:1ω8 c and 18:1ω8 c, respectively) were elevated in CBM‐impacted soils compared with a control site. Comparison of PLFA and 16s rDNA data suggested type I and II methanotroph populations were well estimated and overestimated by their PLFA biomarkers, respectively. The δ 13 C values of PLFAs common in type I and II methanotrophs were as negative as −67‰ and consistent with the assimilation of CBM. PLFAs more indicative of nonmethanotrophic bacteria had δ 13 C values that were intermediate indicating assimilation of both plant‐ and CBM‐derived carbon. Δ 14 C values of select PLFAs (−351 to −936‰) indicated similar patterns of CBM assimilation by methanotrophs and nonmethanotrophs and were used to estimate that 35–91% of carbon assimilated by nonmethanotrophs was derived from CBM depending on time of sampling and soil depth.